2015
DOI: 10.4140/tcp.n.2015.459
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pharmacist Interventions on Herpes Zoster Vaccination Rates

Abstract: The Centers for Disease Control and Prevention found that in 2010 only 14.4% of people in the United States who are appropriate candidates received the herpes zoster (shingles) vaccine. This manuscript highlights recent studies that investigate how pharmacists can help improve vaccination rates of herpes zoster in the geriatric population. Research has demonstrated that face-to-face interaction, education, and outreach by pharmacists in the community can help improve rates of herpes zoster vaccination. Having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The study adds to evidence on the pivotal role of provider recommendations regarding getting the shingles vaccine. Consistent with other studies, receiving advice from a GP or another healthcare provider (HCP) to get the shingles vaccine increases acceptability of the vaccine [15,16,21,38,39], and may even reverse initial reluctance towards the shingles vaccination [14].…”
Section: Discussionmentioning
confidence: 57%
“…The study adds to evidence on the pivotal role of provider recommendations regarding getting the shingles vaccine. Consistent with other studies, receiving advice from a GP or another healthcare provider (HCP) to get the shingles vaccine increases acceptability of the vaccine [15,16,21,38,39], and may even reverse initial reluctance towards the shingles vaccination [14].…”
Section: Discussionmentioning
confidence: 57%
“…Concerning the perspectives of the evolution of recommendations, only about 50% of participants were in favor of a mandatory vaccination or a school-based program. These rates are much lower than those found in other European countries; 77% of gynecologists in Poland [ 83 ] and 91% of health professionals in Italy [ 85 ] are in favor of mandatory vaccination. In addition, several studies suggest that American [ 86 , 87 ] and Australian parents tend to support school-based vaccination programs for their children [ 88 ].…”
Section: Discussionmentioning
confidence: 71%
“…This interest in summary leaflets has also been shown among GPs and pharmacists in New Zealand [ 80 ] and Canada [ 75 ]. In addition, several studies have demonstrated their effectiveness in increasing the acceptability of HPV vaccination [ 81 , 82 ], Herpes Zoster vaccination [ 83 ], or the proper use of antibiotics [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with existing research that demonstrated receiving a recommendation, advice, and education from HCPs improves HZ vaccine uptake and adherence. 11 , 27–29 …”
Section: Discussionmentioning
confidence: 99%